Dietary Calcium and Framingham Risk Score in Vitamin D Deficient Male (KNHANES 2009-2011) - Choi, Sung-Jin (Yonsei Med J, 2015)
PURPOSE: The association between excess calcium intake and cardiovascular mortality has already been reported. In the present study, we investigated the relation between dietary calcium intake and Framingham Risk Score (FRS) according to serum 25-hydroxyvitamin D [25(OH)D] status. MATERIALS AND METHODS: A total of 7809 subjects (3452 males and 4357 female) aged over 40 years were selected for this cross-sectional study from data obtained from the Korea National Health and Nutrition Examination Survey (2008-2011). Daily dietary calcium intake was categorized into <300, 300-600, 600-900, 900-1200, and >1200 mg/day and serum 25(OH)D concentration classified into <50, 50-75, >75 mmol/L. The FRS was compared by the daily dietary calcium intake categories according to 25(OH)D concentration after adjustment with relevant variables in both genders. RESULTS: Higher FRS was observed in males with both <300 mg and >1200 mg of dietary calcium intake and females with <300 mg of dietary calcium intake without adjustment. The significantly higher FRS remained in the <300 mg and >1200 mg of dietary calcium intake groups in both genders after adjustments for relevant variables. FRS was significantly higher in the group with >1200 mg of dietary calcium intake and serum 25(OH)D <50 nmol/L, which was the male only vitamin D deficient group. CONCLUSION: Very low (<300 mg/day) and excess (>1200 mg/day) dietary calcium intake were related with higher FRS in both genders. In particular, higher FRS was observed in the excess (>1200 mg/day) dietary calcium intake male group under vitamin D deficiency (<50 nmol/L).